(untitled) (International relations and international law Journal, 2016)
In this article one of the discriminating phenomena of Israeli defense policy – targeted killings, as a means of Israeli intelligence to combat terrorism and protect national security are considered. The author gives the examples of using this measure in the history of the State of Israel, in particular, during the endless Israeli-Palestinian conflict, and shows the consequences to which these bloody actions have led. Moreover, advantages and disadvantages of using such method in the fight against terrorism have been analyzed from the moral and legal points of view. Furthermore, the effectiveness of this policy and its "conformity" with the Jewish law has been analyzed. In conclusion, the author proves the justification of using the “targeted killings” as last measures to ensure the security and to protect the state and the people.